Whistleblowing, National Security and the Constitutional Freedom of Political Communication. (September 2018) - Ireland-Piper, Danielle; Crowe, Jonathan
Whistleblowers promote the values of responsible government and the rule of law by drawing attention to criminal or other forms of wrongdoing in publicly accountable organisations. This article explores the relationship between whistleblowing, national security and the implied freedom of political communication under the Australian Constitution . Legislation such as the Crimes Act 1914 (Cth) (' Crimes Act '), the Australian Security Intelligence Organisation Act 1979 (Cth) (' ASIO Act' ) and the Australian Border Force Act 2015 (Cth) (' Border Force Act' ) makes it an offence to reveal certain types of information obtained as a Commonwealth officer. The Public Interest Disclosure Act 2013 (Cth) (' PIDA ') offers limited protection to whistleblowers in the Commonwealth public sector, but this protection does not extend to information relating to intelligence operations. We argue that blanket criminalisation of unauthorised disclosure by Commonwealth officers or contractors under s 70 of the Crimes Act, along with similar prohibitions in s 35P of the ASIO Act and s 42 of the Border Force Act, offend the implied freedom of political communication by failing to strike an adequate balance between national security and organisational secrecy, on the one hand, and public debate and discussion, on the other. The courts should read down these laws to protect disclosures that hold significant public interest for discussion and debate over government policy or the performance of government officials.